Beer Drinking Nations. The Determinants of Global Beer Consumption. - Liesbeth Colen; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
In this paper we analyze the evolution of beer consumption between countries and over time. Historically, there have been major changes in beer consumption in the world. In recent times, per capita consumption has decreased in traditional ' beer drinking nations' while it increased strongly in emerging economies. Recently, China has overtaken the US as the largest beer economy. A quantitative empirical analysis shows the relationship between income and beer consumption has an inverse U-shape. Beer consumption initially increases with rising incomes, but at higher levels of income beer consumption falls. Increased openness to trade and globalization has contributed to a convergence in alcohol consumption patterns across countries. In countries that were originally 'beer drinking nations', the share of beer in total alcohol consumption reduced while this is not the case in countries which traditionally drank mostly wine or spirits. Climatic conditions, religion, and relative prices also influence beer consumption.
Keywords: N30; D12; Q11; 330; beer; consumption patterns; history; taste convergence; Bier; Konsum; Ernährungsverhalten; Anpassung; Vergleich; Welt